A Comprehensive Methodological Review of Major Developments in Bioinformatics Pipelines for Transcriptomic Data Analysis - Awais ALi; Syed Luqman Ali; Abdelkarem Omneya (Novelty in Biomedicine)
Background: Recent advances in transcriptomics have provided new insights to analyze a wide range of biological data. RNA sequencing (RNA-Seq) is a common method used to study the complete set of RNA molecules (the transcriptome) in different cell types, genetic backgrounds, and environments. While many computational tools exist for analyzing large RNA-Seq datasets, there is still a need to thoroughly compare methods used to separate mixed cell populations (deconvolution).